2022
DOI: 10.4081/ija.2022.2126
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hail damages in maize using remote sensing and comparison with an insurance assessment: A case study in Lombardy

Abstract: Studies have shown that the quantification of hail damage is generally inaccurate and is influenced by the experience of the field surveyors/technicians. To overcome this problem, the vegetation indices retrieved by remote sensing, can be used to get information about the hail damage. The aim of this work is the detection of medium-low damages (i.e., between 10 and 30% of the gross saleable production) using the much-used normalized difference vegetation index (NDVI) in comparison with alternative vegetation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…It is also revealed that in South America, remote sensing is of great interest to explore vast environmental ecosystems such as the Amazon. For instance, it is used for hail predictions to estimate and control damages [22]. Also, to enhance fishery productivity by mapping water reservoirs [21], and so forth.…”
Section: Author's Abstractmentioning
confidence: 99%
“…It is also revealed that in South America, remote sensing is of great interest to explore vast environmental ecosystems such as the Amazon. For instance, it is used for hail predictions to estimate and control damages [22]. Also, to enhance fishery productivity by mapping water reservoirs [21], and so forth.…”
Section: Author's Abstractmentioning
confidence: 99%
“…However, once the damage caused by an extreme climate event has happened it is important to spatially quantify it. Schillaci et al (2022) used satellite data from Sentinel 2 to evaluate hail damage in several areas. They also evaluated which vegetation index would have the highest accuracy in evaluating the damage.…”
mentioning
confidence: 99%